O uso da mídia na contextualização do ensino de matemática - Camargo Junior, Antonio Carlos (2014)
This work had as its theme the prospect of making the teaching of mathematics attractive, motivating and therefore significant, through approaches inherent in the concept of meaningful learning, and the context of classes with the use of media in the classroom, as it is believed that the school must enter new methodologies that facilitate the integration of media resources in the classroom as teaching strategies conducive for meaningful learning. This insertion was through activities performed by students that consisted in handling printed material and software to enrich the mathematical contents researched in books, newspapers and internet. As a tool for obtaining benchmark to reflect the results of the students opinion, where satisfactory results were obtained, because the students felt motivated and engaged by the activity questionnaire was administered, which has stated a preference for innovative rather than traditional classes to be more interesting and easier to learn with the help of internet and media resources. In this sense it is believed in the validity of the concepts discussed in this work and methodology aimed at contextualizing the mathematical content and the meaning of mathematical concepts researched by students.